DEBT RESTRUCTURING AND STRENGTHENING INTERNATIONAL COOPERATION: A LITERATURE REVIEW OF GLOBAL ECONOMIC RISK MITIGATION STRATEGIES FOR THE 2025 IMF-WORLD BANK MEETINGS - Indra Rachmawati; Lia Lia (CV. Adiba Aisha Amira, 2025)
The global debt crisis and increasing fragmentation of the international economy are the main challenges facing countries in 2025. This research aims to examine debt restructuring strategies and strengthening international cooperation as an effort to mitigate global economic risks, with a focus on the agenda and relevance in the 2025 IMF-World Bank Meetings. Through a literature review of official documents, policy reports, and scientific literature, this research finds that effective debt restructuring requires transparency, broad creditor participation, and an inclusive and adaptive framework. Meanwhile, international cooperation through multilateral forums such as the IMF, World Bank, and G20 has been proven to accelerate the restructuring process, encourage reform of the global financial architecture, and provide technical and financial support to crisis-affected countries. The results of the study confirm that the success of mitigating global economic risks is highly dependent on political commitment, policy innovation, and synergy between countries. Inclusive debt restructuring and strengthened international cooperation are the key foundations for a fair, sustainable and resilient economic recovery.